Self-management education among women with pre-existing diabetes in pregnancy: A scoping review. (May 2021) - Sushko, Katelyn; Menezes, Holly Tschirhart; Strachan, Patricia; Butt, Michelle; Sherifali, Diana
Abstract: Background: Education is a cornerstone of self-management for adults with diabetes. Self-management is particularly important during pregnancy for women with type 1 and type 2 diabetes, as perinatal outcomes are affected by maternal glycemic control. To our knowledge, literature describing the provision of diabetes education and support during pregnancy for women with type 1 and type 2 diabetes has not been synthesized, nor examined within its context as a complex intervention. Objectives and design: This scoping review aims to synthesize the evidence regarding prenatal diabetes education and support for women with type 1 and type 2 diabetes and to apply the Medical Research Council framework for complex interventions where appropriate. Data sources and methods: We searched EMBASE, CINAHL, and MEDLINE from inception to February 2019 for primary studies focused on prenatal diabetes education among women with type 1 and type 2 diabetes. Two independent reviewers screened eligible studies against inclusion criteria. A narrative synthesis of the included studies was conducted. Results: Of 511 identified citations, 30 studies were included in the final review. Approximately 44% of the pooled sample were women with type 1 diabetes, 46% had gestational diabetes mellitus, and 10% had type 2 diabetes. Education focused on self-monitoring of blood glucose, attaining glycemic targets, and following a healthy diet. Many studies included educational elements that went beyond traditional didactic teaching and promoted self-management skills and self-management support. The majority of education was delivered via one-on-one outpatient appointments every one to three weeks. About half of the reviewed studies used a multidisciplinary team approach, with most including a combination of physicians, nurses, dietitians, and midwives. Application of the Medical Research Council framework revealed that most studies were limited in methods (i.e., randomization) and few examined process evaluation or intervention cost-effectiveness. Conclusion: We identified a lack of studies centred on educational interventions for women with type 2 diabetes in pregnancy. As pregnancy for women with type 2 diabetes involves significant changes, including the transition from oral hypoglycemics to insulin therapy, often without exposure to diabetes-specific preconception care and counselling, future research may focus on optimizing preconception and prenatal education and support for this high-risk group. This is particularly relevant as the prevalence of type 2 diabetes is increasing worldwide. Future research ought to also design, implement and evaluate interventions in accordance with the Medical Research Council framework for complex interventions.